Using curriculum-Based Measurements to Assess Reading: The Cultural Connections of Diverse Students with Learning Disabilities - Blue, Elfreda V.; Alexander, Tammy (Journal of the American Academy of Special Education Professionals, 2009)
Students with learning disabilities face real reading challenges. Research into the reading performance of culturally diverse students indicates improved reading performance for culturally diverse students when text matches students’ cultural perspective. This quasiexperimental research investigates whether Caucasian and African American students with learning disabilities read diverse text differently. Curriculum-based measures (fluency level, comprehension score, and meaning-changing deviations) were used to assess reading performance by ethnicity and reading ability. Two-way MANOVA tests yielded interactions for reading ability x passage and reading ability x ethnicity. Results indicate that low achieving readers comprehended more and had fewer meaning-changing deviations when cultural cues were embedded in text. Results of this study indicate that further consideration must be given to the cultural perspective of readers and text used in reading assessment. Generalizations about student reading ability must be contextualized in discussions about the presence or absence of cultural cues in text to be read.